2, 2′-Ethylenebis(1, 3-dithiane) as a polydentate μ2-, μ4- and μ5-assembling ligand for the construction of sulphur-rich Cu(i), Hg(ii) and heterometallic Cu(i)/Hg(ii) coordination polymers featuring uncommon network architectures. Issue 19 (4th May 2022) - Viau, Lydie; Knorr, Michael; Knauer, Lena; Brieger, Lukas; Strohmann, Carsten
Abstract : The coordination chemistry of the polydentate thiaheterocycle 2, 2′-ethylenebis(1, 3-dithiane) L1 towards CuX and HgX2 salts was investigated using different metal-to-ligand ratios. Abstract : With the aim to elaborate novel and inexpensive sulphur-rich materials featuring unusual network architectures, the coordination chemistry of the tetradentate thiaheterocycle 1, 2-di(1, 3-dithian-2-yl)ethane L1 ligand toward CuX and HgX2 salts was investigated. When L1 is reacted with CuI in a 1 : 1 ratio, a two-dimensional CP [{Cu(μ2 -I)2 Cu}(μ2 -L1 )] n (CP1 ) is formed, in which two out of four S atoms of L1 remain non-coordinated. Upon treatment of L1 with CuI in a 1 : 2 ratio, [{Cu(μ2 -I)2 Cu}(μ4 -L1 )] n (CP2 ) is obtained, in which each S atom of L1 coordinates to one copper centre forming a 2D layer. Raising the ligand-to-CuI ratio to 1 : 4 affords the 2D material [{Cu(μ4 -I)(μ2 -I)Cu}2 (μ4 -L1 )] n (CP3 ), in which [Cu(μ4 -I)(μ2 -I)Cu] n ribbons are interconnected through μ4 -bridging L1 ligands. Upon the reaction of L1 with CuBr in a 1 : 2 ratio, a 2D CP [{Cu(μ2 -Br)}2 (μ2 -L1 )(μ4 -L1 )0.5 ] n (CP4 ) is formed at room temperature and a 2D CP [{Cu(μ2 -Br)}2 (μ4 -L1 )] n (CP5 ) is obtained in refluxing propionitrile. In CP4 and CP5 Cu atoms are bridged by a single μ2 -Br ligand giving rise to [Cu(μ2 -Br)Cu] n ribbons but CP4 differs from CP5 from the metal to ligand ratio and the presence of non-coordinated S atoms. Employing a 1 : 3 ratio, a 1D ribbon [{Cu(μ2 -Br)}3 (MeCN)(μ4 -L1 )] n (CP6 ) is generated, that contains both tetrahedral and trigonal copper atoms. CP6 also presents two different L1 ligands that differ by the coordination mode of the sulphur atoms (S acting as 2 or as 4 electron-donor). With CuCl, a 2D network [{Cu(μ2 -Cl)2 Cu}(μ4 -L1 )] n (CP7 ) is generated. L1 coordinates also on HgX2 salts to yield CPs whose architecture depends on the ligand-to-metal ratio. The meander-shaped 1D CP [(HgI2 )(μ2 -L1 )] n (CP8 ) and the linear 1D ribbons of CP9 and CP12 [(HgX2 )(μ2 -L1 )] n (X = Br, Cl) result from treatment with L1 in a 1 : 1 ratio. In the case of HgBr2, using a 2 : 1 metal-to-ligand ratio, 1D polymeric [{BrHg(μ2 -Br)2 HgBr}(μ2 -L1 )] (CP10 ) is produced. HgI2 and HgBr2 have also been reacted with 2-methyl-1, 3-dithiane L2 yielding the molecular complexes [{IHg(μ2 -I)2 HgI}(κ 1 -L2 )2 ] (D1 ) and [HgBr2 (κ 1 -L2 )2 ] (M1 ). Two heterometallic 1D materials [{IHg(μ2 -I)2 HgI(μ2 -I)2 {Cu(RCN)2 }2 (μ2 -L1 )] n (CP13 ) and (CP14 ) result from the treatment of CP1 with HgI2 in MeCN or EtCN. Performing the reaction of CP1 with HgBr2 in acetonitrile produces the zwitterionic 2D material [Cu(MeCN)}(HgIBr2 )(μ2 -L1 )1.5 ] n (CP15 ).